Gynaecomastia: assessment and management. Issue 1 (28th January 2013) - Chicken, Wayne; Davidson, Tim
Abstract Gynaecomastia is the most common breast problem afflicting men. Although the condition can usually be managed within primary care, specialist referral is required if there is any doubt about the differential diagnosis of breast carcinoma or where surgical management is contemplated. Copyright © 2013 John Wiley & Sons